PENGARUH STRATEGI BUNDLING TERHADAP MINAT BELI PRODUK PIJAR SEKOLAH (STUDI KASUS PT TELKOM INDONESIA WITEL BANDUNG TAHUN 2023) - Islammiyah, Nabila; Mustikasari, Ati (eProceedings of Applied Science, 2023)
Keyword: This research aims to investigate the influence of Pijar Sekolah's bundling program within the connectivity package on the purchasing intention of school consumers in the Bandung Telecommunication Area (Witel Bandung), using a case study approach at PT Telkom Indonesia. The research method employed was a survey with sample random sampling technique involving 100 respondents who are customers of Pijar Sekolah package. Data analysis was conducted using simple linear regression analysis. The findings of the study indicate that Pijar Sekolah's bundling program within the connectivity package has a significant influence on the purchasing intention of school consumers in Witel Bandung. Pijar Sekolah provides various benefits, ranging from supporting engaging and enjoyable digital learning, facilitating examination administration, to assisting in the management of school administration and operations. Through the Pijar Sekolah platform, the vision and mission to equalize education in Indonesia and expand technology access in Education 4.0 can be realized.Keyword: Marketing Strategy, Product Value, Marketing Effectiveness, Pijar Sekolah Bundling Program, School Consumer Purchase Intention